Jaringan Advokasi Transnasional dalam Upaya Pelestarian Kawasan Arktik Dari Eksplorasi Minyak di Norwegia Tahun 2016 - 2018 - Meidinda Putri Azura; Triardra, Reza (Department of International Relations, Brawijaya University, 2024)
Abstract Climate change is a global commons problem. Its causes man-made greenhouse gas emissions and impacts are distributed and felt across the earth, transcending traditional boundaries and jurisdictions of the states of the international system. In the case of Norway, the country has been a vocal pioneer for climate action in international forums and has made specific policy progress in that areas. Yet there is significant cognitive dissonance as the country fails to address the impact of its oil and gas extraction, instead facilitating new exploration that is incompatible with global carbon budgets, and indeed undermines global efforts to reduce emissions. For a country so dedicated to its environmental goals, Norway must also decide whether oil and gas investment makes climate sense. Greenpeace Nordic and Nature & Youth (Natur og Ungdom) together with its networks were creating a global movement The People vs. Arctic Oil unites against the state of Norway with the purpose of keeping the world within its environmental boundaries in order to safeguard all life on Earth and to secure a peaceful and sustainable future for the Arctic due to government’s plan to opening new oil excavations in the Arctic breaches in 2016. The idea of communication revolution we find ourselves in may also be changing the power itself, shifting the balance way of view and into the hands of many. This advocacy networks has the ability to create truly transnational movements that has the potential to affect change. This research aims to describing in more depth the concept of Transnational Advocacy Networks by Keck and Sikkink through the case study of strategies that has been used by this advocacy networks in order to reach their goals in advocating the issue regarding their attempt to preserve the Arctic from Norway’s plan to do an Arctic oil exploration. Keywords: Climate Change, Norway, Oil Exploration, Arctic, Advocacy, Transnational Advocacy Networks Abstrak Perubahan iklim merupakan masalah bersama secara global. Hal ini ...